Routinized performances of belonging: Everyday practices and relationships in rural and regional areas during the pandemic. Issue 6 (28th March 2022) - Cook, Julia; Cuervo, Hernan
Abstract: The concentration of COVID‐19 cases and restrictions in metropolitan areas in 2020 resulted in a re‐emergence of the concept of the 'rural idyll' in Australia, with rural and regional areas coming to be associated with a safe and uninterrupted way of life. Implicit in this notion is the assumption that those living in rural and regional areas found their routines and experiences of belonging uninterrupted. We critique this narrative by drawing on qualitative longitudinal data collected from 2006 to 2020, which allows us to examine our participants' experiences of belonging in rural and regional areas both before and during the pandemic. We find that although our participants' experiences of belonging were largely undisturbed by the pandemic, this was not because their lives were not affected more broadly, but because their sense of belonging was established through everyday routines and practices that were maintained during the pandemic.